ARTIFICIAL INTELLIGENCE AND INSTITUTIONAL GOAL ACTUALIZATION OF PROFESSIONAL ACCOUNTING INSTITUTES IN NIGERIA (Journal of Global Accounting, 2025)
Goal actualization facilitates accounting institutes’ ability to meet the needs of present customers while taking into account the needs of future generations. Goal actualization remains a growing field of research in varied organizations in light of the need to achieve and sustain competitive advantage through core competence.  The research design adopted was a cross-sectional survey. The survey was conducted among 90,950 active professional members of the Institute of Chartered Accountants of Nigeria (ICAN) and the Association of National Accountants of Nigeria (ANAN). The sample size of 520 was determined using Taro Yamane formula.  The findings showed that Artificial Intelligence had a positive and significant effect on institutional goal actualization with (R2 = 0.612, Chi_bs (5) = 298.944, p < 0.05), of professional accounting institutes in Nigeria. The study concluded that Artificial Intelligence affected institutional goal actualization of professional accounting institutes in Nigeria. It was recommended that professional accounting institutes should create more public education on the advantages and disadvantages of adopting Artificial Intelligence with a view to positioning stakeholders for seamless adoption of the technology.
Keywords: Accounting Institutes; Artificial Intelligence; Institutional corporate social responsibility; Institutional goals actualization; Institution Sustainability